PENDIDIKAN ANAK DISHARMONISASI RUMAH TANGGA DI MADRASAH SUATU PENDEKATAN INDIVIDUAL - Nazaruddin, M.Ag (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2020)
Family disharmony has an impact on children's education, both positive and negative impacts. However, the more dominant impact resulting from disharmony on children's education is the negative impact. The impact is bias on dropping out of school, lack of control over children's education, loss of passion for children to study at school. Even more severe the impact will make children choose and decide their own life path. The influence of the household on the growth and physical and psychological development of children, teachers must take steps or find solutions so that the education of children who experience household disharmony can achieve their education in accordance with the goals of national education.